2022
DOI: 10.1371/journal.pmed.1003931
|View full text |Cite
|
Sign up to set email alerts
|

Associations between multimorbidity and adverse health outcomes in UK Biobank and the SAIL Databank: A comparison of longitudinal cohort studies

Abstract: Background Cohorts such as UK Biobank are increasingly used to study multimorbidity; however, there are concerns that lack of representativeness may lead to biased results. This study aims to compare associations between multimorbidity and adverse health outcomes in UK Biobank and a nationally representative sample. Methods and findings These are observational analyses of cohorts identified from linked routine healthcare data from UK Biobank participants (n = 211,597 from England, Scotland, and Wales with li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…For example, UK Biobank appears to underestimate the risks of mortality, hospitalisation and MACEs associated with high levels of multimorbidity. 43 It is likely, therefore, that our estimates of the associations between frailty and adverse outcomes may be conservative. UK Biobank spirometry data are also not postbronchodilator; however, we used primary care spirometry data where possible (available for 70% of participants), which has been shown to be of high quality, and our findings were consistent when restricting our analysis to those with primary care spirometry alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, UK Biobank appears to underestimate the risks of mortality, hospitalisation and MACEs associated with high levels of multimorbidity. 43 It is likely, therefore, that our estimates of the associations between frailty and adverse outcomes may be conservative. UK Biobank spirometry data are also not postbronchodilator; however, we used primary care spirometry data where possible (available for 70% of participants), which has been shown to be of high quality, and our findings were consistent when restricting our analysis to those with primary care spirometry alone.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of representativeness may lead to bias in the estimation of associations between exposure and outcomes. For example, UK Biobank appears to underestimate the risks of mortality, hospitalisation and MACEs associated with high levels of multimorbidity 43. It is likely, therefore, that our estimates of the associations between frailty and adverse outcomes may be conservative.…”
Section: Discussionmentioning
confidence: 99%
“…For example if people with either more severe RA or severe frailty were less likely to volunteer for UK Biobank (eg, due to greater functional limitation) this could bias estimates of the association between frailty and RA, as well as the relationship between frailty and adverse outcomes in people with RA. A recent analysis of multimorbidity showed that UK Biobank may underestimate associations between higher long-term condition counts and mortality or hospitalisation 39. The same may be true of frailty in this context, particularly as long-term conditions contribute heavily to the frailty index.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis of multimorbidity showed that UK Biobank may underestimate associations between higher long-term condition counts and mortality or hospitalisation. 39 The same may be true of frailty in this context, particularly as long-term conditions contribute heavily to the frailty index. Finally, our analysis of the frailty phenotype was limited to UK Biobank (as grip strength and walking speed were not assessed in SERA) and analysis of disease activity and change in frailty status was limited to SERA.…”
Section: Rheumatoid Arthritis Rheumatoid Arthritis Rheumatoid Arthritismentioning
confidence: 97%
“…As with any cohort study, the potential for selection bias, such as a healthy volunteer selection bias, cannot be discounted 76 . Participants in the UK Biobank are known to be of higher economic status and to have fewer risk factors related to lifestyle 77 . In addition, UK Biobank participants may be more health-conscious, have fewer comorbidities, and, among older women, be associated with lower all-cause death rates than the general population 76 .…”
Section: Assigning Weights To Each Risk Prediction Tool Improves Disc...mentioning
confidence: 99%